Therapy of post-stroke depression – a systematic review - Wannagat, W.; Zielasek, J.; Gaebel, W. (Die Psychiatrie, 2013)
We performed a systematic review of randomized placebo-controlled pharmacological and non-pharmacological trials for the therapy and prevention of post-stroke depression that have been published between 1980 and 2011. We initially identified 2 260 records of which 28 studies were finally included into this review. A meta-analytic approach was hampered by considerable differences regarding the kinds of therapeutic regimens and the study durations. Modest effects favoring treatment of post-stroke depression could be found for pharmacological treatment as well as repetitive transcranial magnetic stimulation. For the prevention of post-stroke depression, antidepressant pharmacotherapy showed promising results. However, large-scale studies with better standardized study populations, optimized placebo control procedures in non-pharmacological studies, and replication in larger follow-up studies are still necessary to find the optimal therapeutic regimens to prevent and treat post-stroke depression.
Keywords: Post-stroke depression; neuropsychiatry; systematic review; pharmacotherapy; psychotherapy